Buckling of symmetrically laminated quasi-isotropic thin rectangular plates - Altunsaray, Erkin; Bayer, Ismail (TECHNO-PRESS, 2014)
The lowest critical value of the compressive force acting in the plane of symmetrically laminated quasi-isotropic thin rectangular plates is investigated. The critical buckling loads of plates with different types of lamination and aspect ratios are parametrically calculated. Finite Differences Method (FDM) and Galerkin Method are used to solve the governing differential equation for Classical Laminated Plate Theory (CLPT). The results calculated are compared with those obtained by the software ANSYS employing Finite Elements Method (FEM). The results of Galerkin Method (GM) are closer to FEM results than those of FDM. In this study, the primary aim is to conduct a parametrical performance analysis of proper plates that is typically conducted at preliminary structural design stage of composite vessels. Non-dimensional values of critical buckling loads are also provided for practical use for designers.
Keywords: critical buckling load; finite differences method; the Galerkin method; parametric study; symmetrically laminated quasi-isotropic plates; DIFFERENT BOUNDARY-CONDITIONS; INPLANE LOADS; VIBRATION; Construction & Building Technology; Engineering; Materials Science